2017
DOI: 10.1002/adom.201700509
|View full text |Cite
|
Sign up to set email alerts
|

Toward High Uniformity of Photoresponse Broadband Hybrid Organic–Inorganic Photodiode Based on PVP‐Modified Perovskite

Abstract: Broadband photodiode based on Si/perovskite structure that combines the advantages of both silicon and perovskite is presented in this paper. This study addresses the issue of the absent of ultraviolet absorption of silicon and the near‐infrared absorption of perovskite. More significantly, the polyvinyl pyrrolidone (PVP) modification process on the perovskite film shows efficiency on morphology and crystallizing control that are important for high uniformity of responsivity and reproducibility. The result sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…20,21 By combining such perovskites with silicon, much progress in broadband photodetectors has been achieved recently. For instance, Zhao et al reported a CH 3 NH 3 PbI x Cl 3−x /Si hybrid heterostructure photodetector with the poly-vinyl pyrrolidone modification, achieving a wide spectrum response ranging from 405 to 808 nm with a response time of 0.56 ms. 22 By coating Cs-doped FAPbI 3 thin films onto vertical Si nanorods, Xie et al realized a broadband photodetection (300−1150 nm) with the maximum sensitivity at ∼850 nm. 23 By employing the perovskite nanocrystal-embedded composite films as the downshifting materials, Zhong et al realized the enhancement of the UV photoresponse of Si photodetectors, and the light-coupling efficiency at 395 nm was promoted to 80% for the hybrid device.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 By combining such perovskites with silicon, much progress in broadband photodetectors has been achieved recently. For instance, Zhao et al reported a CH 3 NH 3 PbI x Cl 3−x /Si hybrid heterostructure photodetector with the poly-vinyl pyrrolidone modification, achieving a wide spectrum response ranging from 405 to 808 nm with a response time of 0.56 ms. 22 By coating Cs-doped FAPbI 3 thin films onto vertical Si nanorods, Xie et al realized a broadband photodetection (300−1150 nm) with the maximum sensitivity at ∼850 nm. 23 By employing the perovskite nanocrystal-embedded composite films as the downshifting materials, Zhong et al realized the enhancement of the UV photoresponse of Si photodetectors, and the light-coupling efficiency at 395 nm was promoted to 80% for the hybrid device.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the newly emerging metal-halide perovskites (CH 3 NH 3 PbX 3 , CsPbX 3 , X = Cl, Br, and I) have aroused intensive research interest. , Such materials have many appealing properties, such as a large carrier diffusion length, large light absorption coefficients, and low-temperature material-processing methods, and all these merits promote their advances in photodetectors. , By combining such perovskites with silicon, much progress in broadband photodetectors has been achieved recently. For instance, Zhao et al reported a CH 3 NH 3 PbI x Cl 3– x /Si hybrid heterostructure photodetector with the poly-vinyl pyrrolidone modification, achieving a wide spectrum response ranging from 405 to 808 nm with a response time of 0.56 ms . By coating Cs-doped FAPbI 3 thin films onto vertical Si nanorods, Xie et al realized a broadband photodetection (300–1150 nm) with the maximum sensitivity at ∼850 nm .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the tunable photophysical and optoelectronic properties of organic semiconductors, as well as their broad absorption spectra and high photogeneration yields, make them promising active materials for future optoelectronic devices. 21 However, the device performance of organic semiconductor-based photodiodes (OPDs) is still unsatisfactory compared to that of silicon-based ones, mainly due to the relatively high dark current ( J d ) that degrades important figures of merit such as the signal-to-noise ratio, linear dynamic range, and specific detectivity ( D *). 22,23 Therefore, minimizing the dark current is critical for developing OPDs with a performance comparable to or surpassing that of silicon-based photodiodes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, good photodetectors should feature high responsivity, detectivity, and quantum efficiency. For example, photodetectors with broad spectral response from UV to infrared can be used in optical imaging, communication, and so forth, while narrow spectral response photodetectors are necessary in biological detection, environment surveillance, and so forth. Metal-halide perovskites have recently emerged at the forefront of light absorber materials because of their tunable optical band gap, large diffusion length, long carrier lifetime, and so forth, showing great potential as building blocks for efficient photodetectors. However, seeking for the suitable charge carrier acceptors for efficient carrier transportation, tuning spectral response, and high stability remains a daunting task restricting the device performance. , To obtain a solar-blind UV and visible light photodetector, a fluorous polymer was applied as a protection layer, reaching 7.8 A/W for UV light detection . Polyvinyl pyrrolidone (PVP) modification was processed on the perovskite films, showing a wide spectral response from 405 to 808 nm . Other acceptors like conductive metal oxides or low-dimensional semiconductor materials such as MoS 2 and WS 2 suffer from either the inevitable interfacial structural defects, low conductivity, or ambient instability. , …”
Section: Introductionmentioning
confidence: 99%
“…18 Polyvinyl pyrrolidone (PVP) modification was processed on the perovskite films, showing a wide spectral response from 405 to 808 nm. 19 Other acceptors like conductive metal oxides 20 or low-dimensional semiconductor materials such as MoS 2 and WS 2 suffer from either the inevitable interfacial structural defects, low conductivity, or ambient instability. 21,22 Graphene-based materials have long been considered as very promising charge carrier transporters with outstanding chemical stability and high electric conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%